Manajemen sumber daya manusia dalam upaya meningkatkan mutu lembaga pendidikan - An-nuriyah, I'anatul Adhimah (Maliki Interdisciplinary Journal, 2024)
Human resource management in an education institution is a management for the main components as well in organization or institutions, namely people who work individually or in groups within an organization or institution that contribute to achieving a desired goal. Education can also improve the quality of human quality to be a measure of dignity in a nation. In this discussion the aim is to find a source of quality improvement in educational institutions based on training and development planning as well as supporting and inhibiting factors of human resource management in an effort to improve the quality of educational institutions.